PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT KONSUMEN DI PEGADAIAN KOTA BATAM (Studi Kasus Pada Pegadaian Tiban Kampung, Batam Tahun 2012) - Pradana, Ferian Anugrah; Ukhriyawati, Catur Fatchu; Hasibuan, Rahman (University of Riau Kepulauan, 2015)
This research aims to determine the influence of Promotion and Service Quality on Consumer interest in the office of the district of Tiban Kampung Batam City, as well as proving there is or whether the relationship between these variabel as seen from the phenomena that occur in the presence of the costumer in the office the District of Tiban Kampung Batam City.The data are collected with a questionnaire on 87 costumer. Research on data analysis using SPSS version 20. Data collection technique in the quantitative research used is a descriptive analysis and analysis of inferensial.The research resulted in that there was a relationship very closely between promotion (X1) on the consumer interest (Y), There is a positive and significant effect service quality (X2) on the performance of consumer interest (Y). There is a positive and significant effect simultaneously between promotion (X1) and service quality (X2) on the consumer interest (Y) the equation of Yi = 0,385 – X1 (0,007) + X2 (0,796).